Frankenweenie - Burton, Tim, 1958-; Abbate, Allison; August, John.; Ripps, Lenny; Ryder, Winona, 1971-; Short, Martin, 1950-; O'Hara, Catherine; Walt Disney Pictures (Avusturya : Tiglon, 2013)
Young Victor conducts a science experiment that will bring his dog Sparky back to life, only to face unintended, sometimes monstrous consequences.
Originally released as a motion picture in 2012.
Based on a screenplay by Lenny Ripps; based on an original idea by Tim Burton.
Produced by Tim Burton, Allison Abbate ; screenplay by John August ; director of photography, Peter Sorg ; editors, Chris Lebenzon, Mark Solomon ; music, Danny Elfman.
Voices, Martin Short, Catherine O'Hara, Martin Landau, Charlie Tahan, Atticus Shaffer, Winona Ryder.
BBFC code: PG.
Blu-ray Disc, DTS-HD Master Audio 7.1 Dolby Digital; requires Blu-ray player.